Multicenter analysis of soluble Axl reveals diagnostic value for very early stage hepatocellular carcinoma. Issue 2 (13th January 2015) - Reichl, Patrick; Fang, Meng; Starlinger, Patrick; Staufer, Katharina; Nenutil, Rudolf; Muller, Petr; Greplova, Kristina; Valik, Dalibor; Dooley, Steven; Brostjan, Christine; Gruenberger, Thomas; Shen, Jiayun; et al.
<x xml:space="preserve">Abstract</x> If diagnosed at early stages, patients with hepatocellular carcinoma (HCC) can receive curative therapies, whereas therapeutic options at later stages are very limited. Here, we addressed the potential of soluble Axl (sAxl) as a biomarker of early HCC by analyzing levels of sAxl in 311 HCC and 237 control serum samples from centers in Europe and China. Serum concentrations of sAxl were significantly increased in HCC (18.575 ng/mL) as compared to healthy (13.388 ng/mL) or cirrhotic (12.169 ng/mL) controls. Receiver operating characteristic curve analysis of sAxl in very early stage HCC patients (BCLC 0) showed an area under the curve (AUC) of 0.848, with a sensitivity of 76.9% and a specificity of 69.2%. α‐Fetoprotein (AFP)‐negative HCC patients displayed an AUC of 0.803, with sensitivity and specificity of 73% and 70.8%. Combination of sAxl and AFP improved diagnostic accuracy to 0.936 in very early HCC patients and to 0.937 in all HCC. Differential diagnosis of very early HCC versus liver cirrhosis showed a combined performance for sAxl and AFP of 0.901 with a sensitivity of 88.5% and a specificity of 76.7%. Furthermore, sAxl levels failed to be elevated in primary ovarian, colorectal and breast carcinomas as well as in secondary hepatic malignancies derived from colon. In summary, sAxl outperforms AFP in detecting very early HCC as compared to healthy or cirrhotic controls and shows high diagnostic accuracy for AFP‐negative patients. sAxl is specific for HCC and suggested as a biomarker for routine clinical use.